2019
DOI: 10.1021/acs.chemrestox.8b00418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quinone Methide Intermediate Resulting from Metabolic Activation of Icaritin in Vitro and in Vivo

Abstract: Many herbal medicines such as epimedium have been reported to cause adverse effects, and icaritin is the common aglycone of many glucosides in epimedium. Our present work aimed at the clarification of the metabolic activation of icaritin possibly responsible for the adverse effects of epimedium. A quinone methide metabolite (M1) was detected in icaritin-fortified microsomal incubations. A glutathione (GSH) conjugate (M2) and N-acetyl-l-cysteine (NAC) conjugate (M3) derived from icaritin were observed in GSH/NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…The fragment ion of m/z 306.0762 and 272.0885 was produced by glutathione moiety and cleavage of the cysteinyl C-S bond, respectively. The fragment ions observed from the glutathione moiety and cleavage of the cysteinyl C–S bond are the most typical ions found in glutathione conjugates [ 46 , 47 ]. The glutathione conjugate was also observed in the incubation samples with rCYP1A2, rCYP2C19, and rCYP2E1 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The fragment ion of m/z 306.0762 and 272.0885 was produced by glutathione moiety and cleavage of the cysteinyl C-S bond, respectively. The fragment ions observed from the glutathione moiety and cleavage of the cysteinyl C–S bond are the most typical ions found in glutathione conjugates [ 46 , 47 ]. The glutathione conjugate was also observed in the incubation samples with rCYP1A2, rCYP2C19, and rCYP2E1 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the strong covalent effect of isopentenyl, isopentenyl can induce toxicity of cells and mitochondria, leading to cell death . Moreover, the 4-position hydroxyl of Icaritin can cause the production of toxic quinone methide metabolites, which in turn induce liver toxicity . Therefore, we removed isopentenyl and 4-position hydroxyl groups and mainly focused on the optimization of the 2-position, 4-position, and 8-position of Icaritin in order to obtain new compounds with lower toxicity and higher efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the existence of O-quinone metabolite which caused the enzyme inactivation, GSH was used as a trapping agent (Chen et al, 2019). ICT (60 μM), GSH (10 mM), HLM (1.0 mg/ml), MgCl 2 (4.0 mM), PBS (pH 7.4) and NADPH (1.0 mM) were mixed and incubated at 37℃ for 1 h. NADPH was not added in the negative control group.…”
Section: Role Of Human Gsts In the Inactivation Of Reactive O-quinone...mentioning
confidence: 99%
“…In addition, cancer patients are particularly susceptible to drug interactions due to the use of multiple medications and impaired physiological functions (Riechelmann et al, 2007;Conde-Estevez, 2017). Although the role of human P450 enzymes in ICT metabolism appears to be limited, one previous study showed that ICT can be bioactivated into quinone methide (QM) (Figure 1) intermediates by human CYP450 enzymes, which contribute to its adverse effects (Chen et al, 2019). The formation of electrophilic reactive intermediates, such as quinone and its tautomer, has been linked to P450 enzyme inactivation in various cases (Yang et al, 2018;Yadav et al, 2020).…”
Section: Introductionmentioning
confidence: 99%